The Fifth Symposium on Sound Engineering and Mastering; 40th Open Seminr on Acoustics Rzeszów–Polańczyk, 14–17 September, 1993 - SANKIEWICZ, M.; SNAKOWSKA, A. (Archives of Acoustics, 1994)
The Symposium has been organized in common by the Institute of Telecommunication and Acoustics of the Wrocław Technical University, and the Polish AES Section. The debates were held from the 8 till the 10 September 1993 in a conference centre, lovely situated in a garden quarter of Wrocław city, its northeastern part.The jubilee 40th Seminar on Acoustics was held in Polańczyk resort on the Solina Lake in the Bieszczady Mountains. The organizers of the Seminar were: Acoustics Committee of Polish Academy of Science, Institute of Fundamental Technical Research Research, Polish Acoustical Society — Rzeszów Division, and Institute of Physics of the Pedagogical University of Rzeszów.